DESAIN AKUNTANSI ANTI KORUPSI - Taudlikhul Afkar; Johan Wahyu Wicaksono; Ani Faujiah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
The purpose of this study is to design an ideal accounting to prevent corruption. Qualitative research is used for data analysis with sample research on KJKS Manfat and KJKS Harapan Surabaya. Data triangulation is used to collect data, with data validity tests internally, externally, reliably, and objectively. The analysis technique used is taxonomic analysis by explaining in detail the domain of the results of data collection. The results showed that the ideal accounting design to prevent corruption in a cooperative Islamic financial institution is by running an accounting system in accordance with the SOP, making accounting records based on validated transaction evidence, conducting form forms and functions that can only be used by the agency with the authority in accordance with the functional position, then keep records of transaction evidence in the order in which they were made. The treatment of internal control that is not only in compliance with SOPs such as checking all transaction evidence with a record, but by giving a sense of comfort in doing work and rewarding staff through financial adequacy as a preventive measure to prevent fraud committed so that the system runs in accordance with the rules.